2015
DOI: 10.1021/acs.macromol.5b01666
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Cross-Linked Polydimethylsiloxane Networks with Ambient-Temperature Self-Healing

Abstract: Dynamically cross-linked polymer networks have promising potential to serve as self-healing materials, but this is often limited to occur at elevated temperature. We overcome this limitation by refinement of an earlier approach to synthesize dynamically cross-linked polydimethyl­siloxane networks such to show stress relaxation and self-healing at room temperature on short time scales, which we probe by oscillatory shear rheology and piercing experiments. Our studies reveal a direct correlation between the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 114 publications
0
96
0
2
Order By: Relevance
“…Recently,Shimada, Sato et al demonstrated that hydrosilylation of carbonyl compounds,a lso catalyzed by B(C 6 F 5 ) 3 ,c an be combined in tandem with the Piers-Rubinsztajn reaction in the synthesis of oligosiloxanes with perfect control over the oligomer sequence (27,S cheme 4c). [49] Polyhedral oligomeric silsesquioxanes (POSS) are as pecial case of organosilicon compounds with an ordered 3D nanostructure,m ost commonly as ac ubic octamer (31, Figure 6). Shimada et al also demonstrated that, in combination with an iridium catalyst, B(C 6 F 5 ) 3 catalyzes the synthesis of siloxane oligomers with virtually no by-products.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Recently,Shimada, Sato et al demonstrated that hydrosilylation of carbonyl compounds,a lso catalyzed by B(C 6 F 5 ) 3 ,c an be combined in tandem with the Piers-Rubinsztajn reaction in the synthesis of oligosiloxanes with perfect control over the oligomer sequence (27,S cheme 4c). [49] Polyhedral oligomeric silsesquioxanes (POSS) are as pecial case of organosilicon compounds with an ordered 3D nanostructure,m ost commonly as ac ubic octamer (31, Figure 6). Shimada et al also demonstrated that, in combination with an iridium catalyst, B(C 6 F 5 ) 3 catalyzes the synthesis of siloxane oligomers with virtually no by-products.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1][2][3][4] At high temperatures or in the presence of catalysts, chemi cal equilibrations are fast enough to enable large scale reorganization of the network and to relax external stresses. [22,23] These fascinating materials represent therefore an appealing compromise between thermosets (superior solvent and thermomechanical resistance) and thermoplastics (capacity to be dissolved, recycled, and (re) processed). Yet, the covalent network never depolymerizes and a constant number of cross-links is maintained at all times.…”
Section: Introductionmentioning
confidence: 99%
“…To broaden its applications, PDMS elastomers with self‐healing capability can be prepared by incorporating the specific chemical compounds or microencapsulated into PDMS networks. Damages on the elastomer can be healed by adopting different strategies such as tin and platinum‐catalyzed reactions, Diels–Alder reaction, metal‐ligand coordination, reversible acylhydrazone and boroxine bond, and chain exchange and supramolecular chemistry . Nevertheless, the current self‐healing PDMS elastomers suffer from a few drawbacks.…”
Section: Introductionmentioning
confidence: 99%